Simple method for pretreatment of tissue sections for the detection of apoptosis by in situ end-labelling and in situ nick translation. Issue 5 (October 1996) - Panchalingam, S; Reynolds, G M; Lammas, D A; Rowlands, D C; Kumararatne, D S
Abstract : Aims —To overcome the problems associated with proteolytic pretreatment of tissue sections for the detection of apoptosis. Methods —Formalin fixed, paraffin wax embedded tissue sections of reactive lymph nodes and biopsy specimens of Burkitt lymphoma were pretreated by pressure cooking for the detection of apoptosis using the in situ end-labelling and in situ nick translation methods. Results —The results achieved with the in situ end-labelling and nick translations methods were compared with those obtained using a novel anti-apoptosis specific protein (ASP) antibody. The staining patterns generated using the three methods were similar and consistent, although the ASP antibody seemed to be more sensitive and detected higher numbers of apoptotic cells within sections. Conclusions —Pressure cooking is advocated as an alternative method to proteolytic enzyme digestion for pretreating paraffin wax sections. It is reliable, inexpensive, reduces the need to optimise pretreatment variables for different tissues, and permits double immunostaining of sections.